2005
DOI: 10.1080/09585190500239424
|View full text |Cite
|
Sign up to set email alerts
|

The Indian perspective of strategic HR roles and organizational learning capability

Abstract: This study focuses on the empirical analysis of strategic HR roles and organizational learning capability. Line and HR firm performance is further analysed. The sample size consisted of 640 managers in India. Standardized questionnaires were used as tools for the managers' perception of the two variables and their link to data collection. Statistical results indicate that correlation coefficients were mostly significant and positive for the variables and sub-variables of strategic HR roles and organizational l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 126 publications
6
57
0
2
Order By: Relevance
“…Mohrman (2000, 2003) advocate that the HR function will be able to prove its worth and add value to the organization only when it will embrace its new strategic role. In line with that, Bhatnagar and Sharma (2005) demonstrated that the strategic HR roles have a positive impact on the organizations' financial performance. Although a bit more mixed and highlighting the importance of combining both process-and people-oriented roles, the study by Hailey et al (2005) shows how the use of Ulrich's HR roles (1997) may contribute to achieve better organizational performance.…”
Section: Hr Roles and Performancesupporting
confidence: 58%
See 1 more Smart Citation
“…Mohrman (2000, 2003) advocate that the HR function will be able to prove its worth and add value to the organization only when it will embrace its new strategic role. In line with that, Bhatnagar and Sharma (2005) demonstrated that the strategic HR roles have a positive impact on the organizations' financial performance. Although a bit more mixed and highlighting the importance of combining both process-and people-oriented roles, the study by Hailey et al (2005) shows how the use of Ulrich's HR roles (1997) may contribute to achieve better organizational performance.…”
Section: Hr Roles and Performancesupporting
confidence: 58%
“…This model has been widely applied by other researchers (Bhatnagar & Sharma, 2005;Caldwell, 2001;Truss et al, 2002). Respondents specified on a 5-point Table 2.…”
Section: Hr Rolesmentioning
confidence: 99%
“…Perhaps, the emerging concept of 'strategic partner' (Bhatnagar & Sharma, 2005;Buyen & de Vos, 2001;Lawler & Mohrman, 2000;Ulrich, 1997;Wright, Dyer & Takla 1999) contends that HR departments should help line managers resolve business issues and align HR interests with the achievement of organizational goals. Line managers are important for successful policy implementation in organizational change situations, as vital communication link between senior management and team members (McHugh, O'Brien, & Ramondt, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…However, a review of extant literature (Kim & Sung-Choon, 2011;Bhatnagar & Sharma, 2005;Clark and Cooling, 2005;Christiansen, 2008;Scotts, 2008;Aitchison, 2007;Long & Wan Khairuzzaman, 2008;Pietersen & Engelbrecht, 2005) on HR competencies and organizational performance revealed that various studies have been carried out on the required competencies of HR professionals as well as the expected strategic partner role of the HR professionals. Therefore, the need for human resource professionals to become intricate in human resource strategic management (HRM), contributing to organizations competitive advantage, becoming true strategic partners that add value as well as shifting from the transactional functions to transformational role has been the critical issues of debate with the view of making HR truly strategic as there have been serious deliberations regarding the contributions of HR to organizational performance lately (Ulrich et al, 2008).…”
Section: Introductionmentioning
confidence: 99%